Developing new products on time, in time - Cooper, Robert G.
Robert G. Cooper reports study findings that sound business practices for boosting profitability also lead to fast-paced, on-time new product projects.
Most sound business practices that help profitability also lead to fast-paced, on-time products, this study shows. True cross-functional teams lead the way.
Accelerated product development is key to new product success. But most prescriptions for cycle time reduction are based on little hard evidence. This article reports the results of an extensive study of 103 new product projects, with a particular focus on the drivers of both reduced cycle time (on-schedule performance and time-efficient developments) and profitability. The use of a true cross-functional team, undertaking solid up-front homework before development began, a strong market orientation (building in "the voice of the customer"), quality of execution, and getting sharp, early product definition where some of the common ingredients of projects that were both on time and fast to market. While profitability and speed where linked, there was not the one-to-one relationship that many imagine. Finally, developing a unique, superior product which delivered real value to the customer was no less time efficient than developing "me-too" products.
Keywords: New products